The Gastrodynamics of Edna Pontellier’s liberation. - Urszula Niewiadomska-Flis (Transatlantica)
In The Awakening Kate Chopin uses foodways to define and transgress the social and cultural boundaries of acceptable female behavior as well as to reinscribe woman’s identity through the culinary dimension of her heroine’s life. The novelist uses eating and dining scenes as metaphors for Edna Pontellier’s search for her female selfhood and, in a broader perspective, as symbols of the major issue of her own fiction—gender trouble in the South. In this article I will analyze how various dining experiences become metaphors for Edna’s disintegrating marriage; how the liberating exposure to Creole culture and Cajuns’ interstitial social position allows Edna to assert her agency through culinary practices; and, in general, how her journey to self-knowledge and subjectivity within a marriage that has diminished her to non-personhood is framed through foodways.